CONSCIENTIZAÇÃO DOS ASPECTOS FONÉTICO-FONOLÓGICOS DO INGLÊS COMO LÍNGUA ESTRANGEIRA: ANÁLISE EM LIVROS DIDÁTICOS - BUCHENER, LAIS KARINA (2020)
This study approaches the role of phonetic-phonological awareness in foreign language learning as an important tool to help develop the learners’ articulatory habits, intonation, rhythm, analysis and sound production in the target language. The accomplishment of this research is based on studies that legitimate the phonetic-phonological awareness for the foreign language teaching/learning. We investigated how this aspect is inserted in teaching materials available for the public school system. For the analysis corpus we selected the collections “Alive High”, from Editoração SM, and “Learn and Share in English”, produced by Editora Ática, which are provided to schools by the National Textbook Program (Programa Nacional do Livro Didático – PNLD), for the 2018 school year. We observed how the oral communicative component is handled, in the activities proposed as a way to develop the pronunciation for the student who wishes to be able to communicate clearly in the target language. In this analysis we focused, primarily, in how the books approach the phonetic and phonological elements, observing the amounts and manners it happens. Besides that, we verified if the aspects and exercises are really relevant to guide students’ foreign language learning and awareness. The results observed through a quantitative and qualitative analysis demonstrate the resources and progress of the textbook collections analyzed in relation to what has been presented by different authors such as Bauer and Alves (2011), Brawerman-Albini and Kluge (2011); Hashimoto and Neto (2018), Tucunduva (2014), Xavier and Urio (2006), about the little instruction that is given about orality and phonetic-phonological aspects. At the end of our study we present that both textbooks stand out for the space addressed to work with pronunciation and that there is an expressive number of activities that aim to bring awareness in syllabic, inter syllabic and phonic levels. The materials analyzed fulfill the communicative teaching aspects and, beyond that, it is important to highlight that the textbooks from “Alive High” and “Learn and Share in English” collections consider the fact that they are made and destined to the peculiarities of Brazilian English language students in Brazil as an essential element for the foreign language teaching.